Species Identification of Conyza bonariensis Assisted by Chloroplast Genome Sequencing - Wang, Aisuo; Wu, Hanwen; Zhu, Xiaocheng; Lin, Jianmin (Frontiers in Genetics, 2018)
Flaxleaf fleabane (Conyza bonariensis [L.] Cronquist) is one of the most difficult weeds to control worldwide. There are more than 150 Conyza species in the world and eight species in Australia. Correct identification of these species can be problematic due to their morphological similarities especially at seedling stage. Developing a robust genetics – based species identification method to distinguish C. bonariensis from other closely related species is important for early control of weeds. We thus examined the chloroplast (cp) genome of C. bonariensis, aiming to identify novel DNA barcodes from the genome sequences, and use the entire cp genome as a super-barcode for molecular identification. The C. bonariensis chloroplast genome is 152,076 bp in size, encodes 133 genes including 88 protein-coding genes, 37 tRNA genes and 8 ribosomal RNA genes. A total of 151 intergenic regions and 19 simple sequence repeats (SSR) were identified in the cp genome of C. bonariensis, which provides a useful genetic resource to develop robust markers for the genetic diversity studies of Conyza species. The sequence information was used to design a robust DNA barcode rps16 and trnQ-UUG which successfully separated three predominant Conyza species (C. bonariensis, C. canadensis and C. sumatrensis). Phylogenetic analyses based on the cp genomes of C. bonariensis, C. canadensis and 18 other Asteraceae species revealed the potential of using entire cp genome as a plant super-barcode to distinguish closely-related weed species.